Multiple recycle fuel cycle for spent nuclear fuel components incineration in fusion-fission hybrid - Moiseenko, V.Е.; Chernitskiy, S.V.; Ågren, O. (Problems of Atomic Science and Technology, 2022)
A multiple recycle fuel cycle (MRFC) is analyzed using a simple numerical model. A straightforward approach to MRFC has some unfavorable features like strong variation of the neutron multiplication factor and accumulation of americium isotopes which would likely hamper its practical usage. A solution proposed here is addition of ²³⁸U both to initial fuel and the recycled fuel.